PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS KEAMANAN PENGGUNAAN UANG ELEKTRONIK SEBAGAI ALAT PEMBAYARAN YANG SAH - Pradnyana, agung Indra; Novy Purwanto, I Wayan (Kertha Wicara : Journal Ilmu Hukum, 2022)
Perkembangan teknologi sangat mempengaruhi alat pembayaran di Indonesia sehingga memunculkan alat pembayaran baru yaitu uang elektronik. Pengaturan uang elektronik belum mengatur mengenai keamanan dalam penggunaan uang elektronik jika terjadi hal-hal yang tidak diinginkan seperti dicuri dan hilang, hal ini bertentangan dengan tujuan dibentuknya peraturan uang elektronik dalam penyelenggaraan uang elektronik yang aman dan adanya penguatan terhadap prinsip perlindungan konsumen sehingga perlu adanya konstruksi norma dalam peraturan tersebut. Fokus permasalahan dalam hal ini bagaimana karakteristik uang elektronik sebagai alat pembayaran yang sah dan konstruksi norma hukum untuk melindungi pemilik atas hilangnya uang elektronik sebagai alat pembayaran yang sah. Metode penelitian yang digunakan dalam penulisan ini adalah metode penelitian yuridis-normatif yang memiliki arti penelitian hukum kepustakaan dengan mencari jawaban atas rumusan masalah yang ada dengan cara meneliti bahan-bahan kepustakaan sebagai data primer dan sekunder. Hasil studi menunjukan Karakteristik uang elektronik dapat dipersamakan dengan uang kertas dan uang logam yang tidak memiliki keamanan dalam penggunaannya, uang elektronik dapat ditingkatkan keamanannya dikarenakan uang elektronik menggunakan sistem elektronik dalam penggunaannya tidak seperti uang kertas dan uang logam, pemanbahan fitur-fitur dalam uang elektronik dapat meningkatkan keamanan dalam penggunaan uang elektronik dengan cara mengkonstruksi ulang Peraturan Bank Indonesia Nomor 20/6/PBI/2018 tentang Uang Elektronik pada Pasal 46 dengan menambahkan fitur pemblokiran, dan fitur pelacakan.  Kata Kunci: Karakteristrik, Uang Elektronik, Konstruksi Norma, Fitur  ABSTRACT  Technological developments greatly affect payment instruments in Indonesia, giving rise to a new payment instrument, namely electronic money. Electronic money regulations have not regulated the security in the use of electronic money in the event of unwanted things such as being stolen and lost, this is contrary to the purpose of establishing electronic money regulations in the administration of safe electronic money and strengthening the principle of consumer protection so that construction is needed. norms in these regulations. The focus of the problem in this case is how to characterize electronic money as a means of cash payment and the construction of legal norms to protect owners from the loss of electronic money as a means of cash payment. The research method used in this paper is a juridical- normative research method which means library law research by seeking answers to the existing problem formulation by examining library materials as primary and secondary data. The characteristics of electronic money can be equated with paper money and coins that do not have security in their use, electronic money can be increased in security because electronic money uses electronic systems in its use unlike paper money and coins, adding features in electronic money can increase security in use of  electronic money by reconstructing Bank Indonesia Regulation Number 20/6/PBI/2018 concerning Electronic Money in Article 46 by adding blocking features and tracking features. Technological developments greatly affect payment instruments in Indonesia, giving rise to a new payment instrument, namely electronic money. Electronic money regulations have not regulated the security in the use of electronic money in the event of unwanted things such as being stolen and lost, this is contrary to the purpose of establishing electronic money regulations in the administration of safe electronic money and strengthening the principle of consumer protection so that construction is needed. norms in these regulations. The focus of the problem in this case is how to characterize electronic money as a means of cash payment and the construction of legal norms to protect owners from the loss of electronic money as a means of cash payment. The research method used in this paper is a juridical-normative research method which means library law research by seeking answers to the existing problem formulation by examining library materials as primary and secondary data. The characteristics of electronic money can be equated with paper money and coins that do not have security in their use, electronic money can be increased in security because electronic money uses electronic systems in its use unlike paper money and coins, adding features in electronic money can increase security in use of electronic money by reconstructing Bank Indonesia Regulation Number 20/6/PBI/2018 concerning Electronic Money in Article 46 by adding blocking features and tracking features.  Key Words: Characteristics, Norm Construction, Electronic Money, Features